Pengaruh Penambahan Serat Batang Pisang Ketip dan Filler Dedak Padi Terhadap Density, Kekuatan Bending dan Tarik Kompositcore, Sandwich dengan Skin Plywood - Salman Salman; Ahmad Fadly (JURNAL MECHANICAL, 2019)
Fiber-reinforced composite core banana stems with additional filler of husk powder is another way to obtain the expected mechanical behavior of the composite. The aim of this study was to analyze the effect of fiber volume fraction content to density, bending strength and tensile strength of sandwich composite.   Preparation of composite was done by hand lay-up method. Composite material used by banana ketip  fiber and addition of husk powder with variation of fiber volume fraction were 7, 10, and 13 % where husk was constant at 5% with random fiber direction. Tests were conducted by referring to the density est standard (ASTM C 271), bending est (ASTM C 393) and tensile test (ASTM D3039).  The result showed that the greater volume fraction of banana fiber, the lower the density value and the lower the bending strength. Whereas the tensile strength tended to increase as the volume fraction was higher.